Lifetime prediction of reinforced concrete structures in carbonation environments carbonation modelling vs air permeability modelling - Faustino, Pedro; Gonçalves, Fábio; Brás, Ana; Nunes, Ângela (Journal of Civil Engineering and Management, 2017)
This article compares two models for the prediction of lifetimes of reinforced concrete structures in carbonation environments based on different tests: carbonation test-based modelling and air permeability test-based modelling. The study also includes experimental testing of five concrete mixes with different types of cement in order to validate the models using safety factors. The tests included compressive strength, accelerated carbonation and air permeability. Both models are defined in a European standard as being alternative to each other, meaning that their results for the same concrete composition and the same environment should converge. The results show that both current models can scarcely constitute alternative to each other. Design lifetime results are far from similar for each concrete mix and each exposure class. The different nature of each test – accelerated carbonation and air permeability – and their different characteristic such as the scattering of results and the unrelated parameters of the modelling equations are some of the features discussed, including the possibility of using different safety factors as function of the model and definition of possible correlation between tests.